Patricia Hayes and Gary Minkley (eds), Ambivalent: Photography and Visibility in African History (Athens, OH: Ohio University Press, 2019), 376 pp, paper back: 978- 0-8214-2394-3, hardcover: 978-0-8214-2393-6, electronic: 978-0-8214-4688-1 - Truscott, Ross (Kronos: Southern African Histories, 2021)
Ambivalent: Photography and Visibility in African History is a collection of essays by young scholars who, with one or two exceptions, work on the African continent. It is the result of sustained collaborative work in and around the Centre for Humanities Research and the History Department at the University of the Western Cape (UWC), and between editors Patricia Hayes and Gary Minkley, who hold NRF SARChI Chairs in Visual History and Theory at UWC, and Social Change at the University of Fort Hare, respectively. It is a profound collaborative scholarly intervention that emerges from this vantage point, from Africa, and from two historically black universities.